A Reliable Design of Water Quality Monitoring System for Online River Data Monitoring (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In Malaysia, the river water pollution problems are getting worse due to the rapid growth of population and urbanization. Lots of human wastes are flowing or poured into rivers including industrial, commercial, domestic and transportation wastes. The pollution of river water has brought many significant effects towards us and the environment. Hence, a real time monitoring system is required to ensure the quality of river water. In this paper, a portable online river water quality monitoring system is presented using IoT technology. The system consists of a microcontroller, several sensors and a Wi-Fi module. The prototype developed is able to measure the parameters like pH, temperature and turbidity of the river water and send to the end users via Wi-Fi. The uniqueness of the device is the mechanism is designed to make it operates reliably in the river in any weather condition and also easy in term of the installation at the site area.